Penerapan Spiral Flounce pada Evening Dress dengan Tema Lucullian of Camelia - Putri Berlian Budi Kanaya; Yuhri Inang Prihatina (BAJU: Journal of Fashion and Textile Design Unesa, 2023)
This research aims to find out the application process and the finished evening dress with Camelia flower as the source of the idea using the spiral flounce technique. The research method used is Double Diamond, which consists of 4 stages discover, define, develop, and deliver. The discover stage searches for and collects inspiration about the characteristics of Camellias, Define and determines the source of ideas to be used as a mood board, determines the color plan and materials, makes an illustration design by the head of thoughts, develops, and determines the illustration design, production design, and spiral flounce trials, the last stage delivers the completion of the finished fashion with Camellia flower inspiration. The finished result of the evening dress showed that it was as expected, namely a dress with an L silhouette using a v-neck, using red color with sequins and lace decoration that successfully created a luxurious impression (lucullian) and beautified the appearance of the outfit. Spiral flounce applied on the right, and left sleeves applied the principles of balance that formed the silhouette of the Camellia flower. The finished product met the desired. Keywords: spiral flounce, evening dress, lucullian, camelia flower